Risk of arrhythmia in type I myotonic dystrophy: the role of clinical and genetic variables. Issue 7 (22nd February 2009) - Cudia, P; Bernasconi, P; Chiodelli, R; Mangiola, F; Bellocci, F; Russo, A Dello; Angelini, C; Romeo, V; Melacini, P; Politano, L; Palladino, A; Nigro, G; et al.
Abstract : Objective: To examine the association between the presence of arrhythmia in type 1 myotonic dystrophy (DM1) and clinical–genetic variables, evaluating their role as predictors of the risk of arrhythmia. Methods: 245 patients with genetically proven DM1 underwent clinical and non-invasive cardiological evaluation. Severity of muscular involvement was assessed according to the 5 point Muscular Disability Rating Score (MDRS). Data were analysed by univariate and multivariate models. Results: 245 patients were examined and cardiac arrhythmias were found in 63 subjects, 40 of whom required a device implant. Statistical analyses revealed that men had more than double the risk of developing arrhythmias compared with women (p = 0.018). Addition of each year of age caused an increased risk of arrhythmia equal to 3% (p = 0.030). Subjects with MDRS 5 had a risk of arrhythmia 12 times higher than patients with MDRS 1–2 (p<0.001). Although all of these variables were significantly associated with cardiac rhythm dysfunction, they had a low sensitivity for the prediction of arrhythmic risk Conclusion: Male sex, age and muscular disability were strongly associated with the development of arrhythmia in DM1. However, all of these variables were weak predictors of arrhythmic risk. These results suggest that other factors may be involved in the development of cardiac conduction abnormalities in DM1.